1997
DOI: 10.1073/pnas.94.23.12467
|View full text |Cite
|
Sign up to set email alerts
|

Intron self-complementarity enforces exon inclusion in a yeast pre-mRNA

Abstract: Skipping of internal exons during removal of introns from pre-mRNA must be avoided for proper expression of most eukaryotic genes. Despite significant understanding of the mechanics of intron removal, mechanisms that ensure inclusion of internal exons in multi-intron pre-mRNAs remain mysterious. Using a natural two-intron yeast gene, we have identified distinct RNA-RNA complementarities within each intron that prevent exon skipping and ensure inclusion of internal exons. We show that these complementarities ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 45 publications
7
65
0
Order By: Relevance
“…34 Indeed, some examples have indicated that RNA secondary structures are involved in splicing regulation. 7,8,19,21,[35][36][37][38] In yeast, new discoveries using high-throughput sequencing have lent strong support to the general hypothesis that the information encoded in large mRNAs is regulated and organized by RNA structure. 39 Therefore, RNA secondary structure strongly contributes to alternative splicing regulation in higher organisms.…”
Section: Resultsmentioning
confidence: 99%
“…34 Indeed, some examples have indicated that RNA secondary structures are involved in splicing regulation. 7,8,19,21,[35][36][37][38] In yeast, new discoveries using high-throughput sequencing have lent strong support to the general hypothesis that the information encoded in large mRNAs is regulated and organized by RNA structure. 39 Therefore, RNA secondary structure strongly contributes to alternative splicing regulation in higher organisms.…”
Section: Resultsmentioning
confidence: 99%
“…1A, scheme i; Materials and Methods). Levels of Dyn2-Cup1 mRNA measured by reverse transcription (RT) by using a primer specific to CUP1 (Howe and Ares 1997) show that the internal exon is efficiently included in the mRNA (E2+; Fig. 1B, lane 1).…”
Section: Resultsmentioning
confidence: 99%
“…There are at least eight two-intron genes in S. cerevisiae (Blandin et al 2000;Davis et al 2000); thus, there are at least eight internal exons for which inclusion in the mature mRNA must be enforced. We previously found that exon inclusion in the two-intron YL8A (RPL7A) pre-mRNA in yeast is enforced in cis by intron selfcomplementarities that orchestrate correct pairing between each set of splice sites (Howe and Ares 1997). This mechanism is inadequate for genes such as DYN2 (Dick et al 1996), which clearly lack intron self-complementarities.…”
Section: Introductionmentioning
confidence: 99%
“…The hnRNP A1 protein has also been implicated in the control of 39 splice site use (Bai et al+, 1999;Caputi et al+, 1999;Del Gatto-Konczak et al+, 1999;Bilodeau et al+, 2001;Tange et al+, 2001;Zhu et al+, 2001)+ In several of these cases, high-affinity A1 binding sites located in the exon near the target 39 splice site have been identified+ In the HIV-1 tat exon 3, recent studies have reported that a high-affinity A1 binding site can antagonize the interaction of SC35 with a nearby enhancer element (Zhu et al+, 2001), and that A1 binding sites in the intron near the 39 splice junction can compromise U2 snRNP binding to the branch site (Tange et al+, 2001)+ Thus, hnRNP A1 may employ different strategies to control splicing decisions depending on the position of high-affinity binding sites and the proximity of other cis-acting elements and trans-acting factors+ Such versatility has also been observed for the RNA binding protein ASF/SF2, which mediates exon enhancer activity in many systems but can also function as a repressor in some pre-mRNAs+ HnRNP A1 could therefore directly interfere with the binding of specific splicing factors in some situations, whereas in others, interactions between distantly bound hnRNP A1 molecules could change the conformation of premRNAs to help carry out switches in splice site selection+ Finally, it is worth noting that the frequency of putative A1 binding sites is high in introns, particularly near splice junctions (Blanchette & Chabot, 1999)+ Thus, in addition to a role in splice site selection, an interaction between bound A1 proteins (and possibly other A1-related hnRNP proteins) may help loop out introns to facilitate commitment between distant splice sites in a manner that is similar to short RNA duplexes in yeast introns (Newman, 1987;Libri et al+, 1995;Charpentier & Rosbash, 1996;Howe & Ares, 1997)+ We are currently exploring the role of high-affinity A1 binding sites in the splicing of large introns+ Because a splice site positioned in a loop becomes repressed, the A1/A1 interaction may also contribute toward preventing the utilization of splice site-like sequences that are invariably present in long introns+…”
Section: Repression Of a Looped Out 59 Splice Sitementioning
confidence: 99%